DNA Methylation Markers and the Identification of Buccal Samples for Forensic Tissue Determination - Kuppareddi Balamurugan; Elizabeth Staples; Hussain Alghanim; George Duncan; Bruce McCord (Forensic Sciences)
Background: The identification of body fluids collected from crime scenes is crucial for determining the type and nature of assaults and for advancing the resolution of crimes. Objectives: The primary aim of this study was to investigate tissue-specific DNA methylation markers that can effectively distinguish buccal samples from blood, semen, and vaginal epithelial tissue. Methods: We screened various markers and selected four genomic locations for further analysis. Genomic DNA was extracted from tissue samples, followed by bisulfite conversion, locus-specific polymerase chain reaction (PCR) amplification, and pyrosequencing. Results: Four loci—cg-9652652, cg-11536474, cg-3867465, and cg-10122865—along with several adjacent CpG sites, were found to be hypermethylated in buccal samples compared to other tissue types. The difference in DNA methylation of buccal samples was statistically significant (p < 0.0001) compared to other tissues, indicating the potential usefulness of these loci for forensic tissue identification. Two additional studies were conducted: (a) a species specificity study and (b) a mixture study involving two different tissue types. The species specificity study showed that the primers used in the assay were specific to primates and humans. They did not amplify five non-primate samples, while the two primate samples—chimpanzee and rhesus—provided usable methylation data. The mixture study involved DNA from two different tissues—buccal samples and semen—combined in varying proportions. The results showed a decrease in the overall percentage of DNA methylation at the locus cg-9652652 as well as five adjacent CpG sites when the amount of buccal cell DNA in the mixture was reduced. Conclusion: The specificity of the primers and the significant differences in percent DNA methylation between buccal cells and other tissues make these markers excellent candidates for forensic tissue identification.